2001
DOI: 10.1063/1.1334636
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of films and solid particles polymerized in fluorocarbon plasmas

Abstract: In fluorocarbon ͑C 4 F 8 ) plasmas, formation mechanisms of polymers were investigated by the characterization with x-ray photoelectron spectroscopy ͑XPS͒ and gel permeation chromatography ͑GPC͒. The molecular compositions of the polymers in the films deposited on the substrate and in the particles formed in the gas phase were elucidated by these chemical analyses. The XPS results showed that the particles were carbon-rich and composed of highly branched molecules in contrast to the film composition. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…We note that existing models 26,37 considered averaged plasma parameters, and we investigated self-consistently the cross-sectional profiles of the governing quantities. The model can be straightforwardly extended to other reactive plasmas containing charged powder, such as the hydrocarbon-3 and fluorocarbon-based 63 powder generating systems. In summary, we have studied the role of the plasma parameters in the management of nanosize powder particles in a low-pressure parallel-plate silane discharge.…”
Section: Discussionmentioning
confidence: 99%
“…We note that existing models 26,37 considered averaged plasma parameters, and we investigated self-consistently the cross-sectional profiles of the governing quantities. The model can be straightforwardly extended to other reactive plasmas containing charged powder, such as the hydrocarbon-3 and fluorocarbon-based 63 powder generating systems. In summary, we have studied the role of the plasma parameters in the management of nanosize powder particles in a low-pressure parallel-plate silane discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In these r.f. plasmas, FC films may be deposited using various fluorocarbon or FC-containing gases such as CF 4 [6], C 2 F 6 [6,7], C 3 F 8 [8], C 4 F 8 [8,9], C 3 F 6 O [10], CH 2 F 2 [11], C 2 H 2 F 4 [11,12], and CHF 3 [13]. These FC gases were decomposed into various radicals and ions, which resulted in the successful fabrication of the films with low dielectric constants.…”
Section: Introductionmentioning
confidence: 99%
“…Though this is not as desirable as conducting a least-squares-fit over a large database of molecules, Cohen and Benson [25] found that GAVs determined from accurate data for single molecules were able to reproduce the thermodynamic properties of larger molecules within experimental uncertainty. Given the fluorocarbon-fluorocarbon interaction values determined by Yamada and Bozzelli [18], GAVs for C-[F] 3 2 were found from C 3 F 6 . The results are listed in table 3, which gives GAVs for standard enthalpies of formation and entropies at 298 K, and molar heat capacities over the range 300 to 1500 K. …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we supposed that setting the GAVs for C-[F] 3 From these assumptions, a step-by-step approach was used to derive group additivity values from the available database. Though this is not as desirable as conducting a least-squares-fit over a large database of molecules, Cohen and Benson [25] found that GAVs determined from accurate data for single molecules were able to reproduce the thermodynamic properties of larger molecules within experimental uncertainty.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation